Sustainable Technology and Innovation - Dr. Preeti Bisen (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2025)
This research paper explores the significance of sustainable technology and innovation in addressing global challenges such as climate change, resource depletion, and environmental degradation. It emphasizes the integration of renewable resources, innovative practices, and eco-friendly technologies to achieve a balance between environmental preservation, economic development, and societal well-being. This study highlights the role of innovations in e-waste management, water conservation, and green manufacturing in building a sustainable future.